ANALISIS CEMARAN MIKROBA PADA DAGING AYAM BROILER DI BEBERAPA PASAR KOTA AMBON - Isye Jean Liur; Astri D. Tagueha (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
Chicken meat is one of the foods favored by the public because it has high nutritional content, delicious taste, affordable prices, and a soft fiber texture that makes it easy to digest. The high nutritional content can make chicken meat a good medium for the growth and development of microorganisms.The research was conducted to determine the amount of bacterial contamination in broiler meat sold in several markets in Ambon city. This study used an experimental method, namely the analysis of microbial contamination in the famous chicken meat sample in Ambon City. The research was started by taking samples of chicken breasts and thighs from various markets in Ambon city. The sample used was chicken meat that had been stored for 2 days. Furthermore, the bacterial isolation stage is carried out. The results showed that the microbial contamination in the sample of chicken breasts and thighs was still below the maximum limit (less than 1 x 106 cfu/g) determined by the National Standardization Agency. Broiler chicken meat in Ambon City is safe for consumption by the public.